Cognitive decline following major surgery is associated with gliosis, β-amyloid accumulation, and τ phosphorylation in old mice - Wan, Yanjie; Xu, Jing; Meng, Fanzhen; Bao, Yuhua; Ge, Yeying; Lobo, Niyati; Vizcaychipi, Marcela P; Zhang, Denghai; Gentleman, Steve M; Maze, Mervyn; Ma, Daqing (Critical care medicine, 2010)
Elderly patients undergoing major surgery often develop cognitive dysfunction and the mechanism of this postoperative complication remains elusive. We sought to determine whether postoperative cognitive dysfunction in old mice is associated with the pathogenesis of Alzheimer's disease. Prospective, randomized study. University teaching hospital-based research laboratory. One-hundred and twenty C57BL/6 14-mo-old male mice (weighing 30-40 g). Mice received intraperitoneal injections of either vehicle or Celastrol (a potent anti-inflammatory compound) for 3 days before undergoing sham surgery or partial hepatectomy, on the surgery day, and for a further 4 days after surgery. Cognitive function, hippocampal neuroinflammation, and pathologic markers of Alzheimer's disease were assessed 1 day after surgery day 1, 3, or 7. Cognitive impairment following surgery was associated with the appearance of certain pathologic hallmarks of Alzheimer's disease: microgliosis, astrogliosis, enhanced transcriptional and translational activity of β-amyloid precursor protein, β-amyloid production, and τ protein hyperphosphorylation in the hippocampus. Surgery-induced changes in cognitive dysfunction were prevented by the administration of Celastrol as were changes in β-amyloid and τ processing. These data suggest that surgery can provoke astrogliosis, β-amyloid accumulation, and τ phosphorylation in old subjects, which is likely to be associated with the cognitive decline seen in postoperative cognitive dysfunction.